Diabetic Gastroenteropathy: Soothe the Symptoms or Unravel a Cure? - Meling, Sondre; Bertoli, Davide; Sangnes, Dag A.; Brock, Christina; Drewes, Asbjørn; Ejskjaer, Niels; Dimcevski, Georg; Søfteland, Eirik (Current Diabetes Reviews, 2022)
Autonomic neuropathy in patients with diabetes mellitus, and especially complications related to gastrointestinal neuropathy, are often overlooked in the clinic. Diabetic gastroenteropathy affects every segment of the gastrointestinal tract and generates symptoms that may include nausea, early satiety, vomiting, abdominal pain, constipation, and diarrhea. Severe cases can be complicated by weight loss, dehydration, and electrolyte disturbances. The pathophysiology is complex, the diagnostics and treatment options are multidisciplinary, and there is generally a lack of evidence for the treatment options. The aims for this review are first to summarize the pathophysiology and describe possible and expected symptoms and complications.Further, we will try to supply the clinician with a straightforward tool for diagnostics, and then, we shall summarize established treatment options, including diet recommendations, pharmacological and non-pharmacological options. Finally, we will explore the multiple possibilities of novel treatment, looking at medications related to the pathophysiology of neuropathy, other manifestations of autonomic neuropathies, and symptomatic treatment for other gastrointestinal disorders, also including new knowledge of endosurgical and neuromodulatory treatment. The overall goal is to increase awareness and knowledge on this frequent diabetic complication and to provide better tools for diagnosis and treatment. Ultimately, we hope to encourage further research in this field, as there are clear shortcomings in terms of biomarkers, pathophysiology, as well as treatment possibilities. In conclusion, diagnosis and management of diabetic gastroenteropathy are challenging and often require multidisciplinary teams and multimodal therapies. Treatment options are sparse, but new pharmacological, endoscopic, and neuromodulatory techniques have shown promising results in initial studies.
Keywords: diabetic gastroenteropathy